The Effect of Caffeic Acid on the Morphometrical Changes of Ovarian Follicles in Premature Ovarian Insufficiency Model of Mice - Reza Javanshir; Hossein Kalarestaghy; Ramin Salimnejad (Journal of Ardabil University of Medical Sciences)
Background: Premature ovarian insufficiency (POI) is the cessation of ovarian function in women under 40. One of the mechanisms involved in the induction of POI is oxidative stress. This study aims to investigate the effect of caffeic acid on the morphometrical changes of ovarian follicles of POI model mice. Methods: Thirty-two female mice were randomly divided into 4 groups (n=8): 1) Control group (cont), 2) Caffeic acid group (CAF), 3) Premature ovarian insufficiency group (POI), and 4) Premature ovarian insufficiency + Caffeic acid group (POI+CAF). POI was induced through daily subcutaneous injections of D-galactose (200 mg/kg) for 6 weeks. Caffeic acid (60 mg/kg, intraperitoneal) was injected daily for 4 weeks from 15th day. One day after the last injection, the mice were anesthetized and the ovaries were removed. Then, the morphometric changes of ovarian follicles were examined using hematoxylin-eosin (H&E) staining. Results: The results showed that D-Galactose-induced POI significantly decreases the diameter of primary, secondary, and antral follicles (P<0.05). Administration of caffeic acid in the POI+CAF group significantly prevented the reduction of follicle diameter (P<0.05). Conclusion: The results showed that caffeic acid can prevent the reduction of the diameter of ovarian follicles in POI model mice.